HYGINE DAN SANITASI DI AREA KITCHEN HOLIDAY INN BANDUNG PASTEUR PADA MASA PANDEMI COVID-19 - Raden Intan Medya Ratna Pury; Ahmad Salman (JURNAL PARIWISATA VOKASI, 2022)
ABSTRACT The tourism sector contributes to the development of Bandung as a tourist city. The tourism industry is expected to continue to contribute to local revenue (PAD). Cleanliness and service to tourists need to be optimized because it will lead to satisfaction, and from satisfaction will cause tourists to return to the city of Bandung. The Covid-19 pandemic that has hit the world today has had a significant impact on all business sectors in the world, including the tourism sector in Indonesia. The hospitality industry in the city of Bandung was greatly affected. Hotel entrepreneurs, restaurant entrepreneurs, restaurant entrepreneurs, hotel and restaurant associations, as well as the government have consulted in reducing the increasingly large losses due to this Covid-19 Pandemic. In this study, the research method used is a descriptive method to describe the factual conditions regarding the process of implementing hygiene and sanitation in hotel kitchens during the Covid-19 pandemic. The data analysis technique used in this study is a qualitative analysis technique. Triangulation technique is used as a technique to check the validity of the data. Keywords: Hygiene and Sanitation. Hygiene Quality. Kitchen Operational Standards. Hotel Kitchen.